Effect of annealing ambient gases on the bias stability of amorphous SnSiO thin-film transistors. (22nd September 2020) - Yang, Jianwen; Cao, Duo; Lin, Dong; Liu, Feng
Abstract: The effect of different annealing ambient gases on the initial electrical properties and bias stability of amorphous tin silicon oxide ( a- SnSiO) thin-film transistors (TFTs) is examined in this study. At an annealing temperature of 350 °C, the SnSiO film remained amorphous with excellent transmittance regardless of the annealing environment. The presence of oxygen during annealing (such as in air and O2 ) could reduce the mobility of the TFTs and create more oxygen-related defect states, thereby reducing the bias stability. In contrast, nitrogen-annealed TFTs showed maximum mobility and optimal bias stability. The corresponding mobility reached 8.6 cm 2 V −1 s −1, the threshold voltage was 0.2 V and the subthreshold swing value was 0.7 V dec −1 .